(3GdTQcGJ GdJLGQjI habG dfXGe GdTQcGJ GdSYhOj (B:s (3GdCMcGe GdYGeI hGdNGUI (B= Trade companies in the Saudi companies law : general and private provisions /s - (3GdNQGHTI, SGej eMeOs ((3YeGf, GdCQOf (B:s (3OGQ GdKbGaI ddfTQ hGdJhRjY,s, 2015)
(3jJfGhd cJGH (B((3GdTQcGJ GdJLGQjI habG dfXGe GdTQcGJ GdSYhOj(B) (3hGdPj bGeg HJCdjag (B((3SGej eMeO GdNQGHTI(B) (3aj MhGdj (B(304) (3UaMI ef GdbWY GdeJhSW ehVhY (B((3GdeDSSGJ GdJLGQjI bhGfjf hJTQjYGJ GdSYhOjI(B) (3eSJYQVG GdeMJhjGJ GdJGdjI (B: (3GdCMcGe GdYGeI ddTQcGJ GdJLGQjI, GdeHMK GdChd (B: (3JCSjS GdTQcGJ GdJLGQjI, GdeWdH GdChd (B: (3YbO GdTQcI , GdaQY GdChd GdCQcGf GdehVhYjI dYbO GdTQcI, GdaQY GdKGfj (B: (3GdCQcGf GdTcdjI dYbO GdTQcI GdaQY GdKGdK (B: (3HWdGf YbO GdTQcI , GdeWdH GdKGfj (B: (3GdTNUjI GdeYfhjI ddTQcI , GdaQY GdChd (B: (3GcJSGH GdTNUjI GdeYfhjI hfgGjJgG , GdaQY GdKGfj (B: (3GdBKGQ GdbGfhfjI GdeJQJHI Ydi GcJSGH GdTNUjI GdeYfhjI, GdeHMK GdKGfj (B: (3GdCMcGe GdYGeI dGfbVGA GdTQcGJ GdJLGQjI hGdBKGQ GdeJQJHI YdjgG(B... (3EdN(B.s
(3HHdjhLQGajI (B: (3UaMI (B299-304.s
Keywords: (3GdeDSSGJ GdJLGQjIs -- (3bhGfjf hJTQjYGJs -- (3GdSYhOjIs; (3GdbGfhf GdJLGQjs -- (3GdSYhOjIs